Opting for partnership governance innovations in Southeast Asia - Gonzales, Joaquin Lucero III; Lauder, Kathleen; Melles, Brenda (Ottawa, Canada Institute on Governance, 2000)
In today's global society, communities are forming synergistic partnerships among other state players so creating stronger economies and offer residents a higher quality of life. This book explores the dynamics of such new partnerships through six case studies in communities in Southeast Asia.
The Baguio Regreening Movement and the Eco-Walk Project : Baguio, Philippines -- Engaging communities in waste management: a holistic and integrated approach : Guimaras, Philippines -- The Vietnam Business Council: collaborative policy-making and information sharing: Hanoi, Vietnam -- Democratic planning using a provincial civic assembly: Khon Kaen, Thailand -- Grassroots governance in rural Thailand: protecting razor clams in Tambol Bangchakreng : Bangchakreng, Thailand -- The sustainable Penang initiative: involving citizens in the development planning process : Penang, Malaysia.
Co-published for distribution by Institute of Southeast Asian Studies.
Includes bibliographical references.
Keywords: Sustainable development -- Southeast Asia -- Citizen participation; Community development -- Southeast Asia; Economic development projects -- Southeast Asia